Al-Farabi’s Thoughts on the Meaning of Life and Freedom: Its relevance to the Existential Crisis in the Digital Era - Fauzan Akbar Novianto (Aqlania, 2025)
The digital era presents new existential challenges for individuals, such as identity crises, the loss of life’s meaning, and dependence on digital validation. These issues reflect how modern humans often fall into artificial forms of existence and lack ethical orientation. This article aims to examine how Al-Farabi’s thought, particularly his concepts of happiness (al-sa‘ādah), the active intellect (al-‘aql al-fa‘āl), and freedom accompanied by moral responsibility, offers an alternative framework of existential philosophy in addressing such issues. This study uses a qualitative method with a literature review approach on Al-Farabi’s significant works, such as Tahṣīl al-Sa‘ādah, Risālah fī al-‘Aql, and Kitāb al-Millah. The findings reveal that although Al-Farabi is not classified within Western existentialism, his philosophical perspectives provide ontological and ethical foundations that can be contextualized to foster self-awareness, autonomy, and the pursuit of a meaningful life amidst digital disruption. This article contributes a fresh discourse in contemporary Islamic philosophy by positioning Al-Farabi as a philosophical reference in facing existential challenges in the digital age.